High effects of climate oscillations on population diversity and structure of endangered Myricaria laxiflora - Li, Hao; Huang, Guiyun; Qiu, Liwen; Liu, Jihong; Guo, Yinhua (Frontiers in Plant Science, 2024)
Exploring the effects of climate oscillations on the population diversity and structure of endangered organisms in the Three Gorges Reservoir area (TGR) is essential for hydrological environment changes on endangered organism evolution. Myricaria laxiflora is an endemic and endangered shrub restricted to the TGR along the banks of Yangtze River, China. Recently, six natural populations of this species were newly found upstream and downstream of the TGR, whose habitats have been dramaticly changed by the summer flooding regulated by large dams. To study the water level fluctuations and climatic shifts on the genetic diversity and genetic differentiation of the six natural populations, 303 individuals from six populations were analyzed based on one nuclear DNA (ITS) and four chloroplast fragments (trnL-F, psbA-trnH, rps16 and rpl16). The phylogenetic tree and significant genetic divergence identified in the cpDNA and ITS with genetic isolation and limited gene flow among regions, suggested that the six populations separated well to two groups distributed upstream and downstream. The maxent modeling results indicated that obvious unidirectional eastward migration via Yangtze River gorges watercourse-mediated from LIG to LGM were showed with the narrow scale distributions of six remnant populations and nine extirpated populations. The initial habitat fragmentation could be triggered by the accumulation of local habitat loss of the impoundment of the TGR during the Present period, and might remain stable restoration with bidirectional diffusion in the Future. Divergences among M. laxiflora populations might have been induced by the drastic changes of the external environment and limited seed/pollen dispersal capacity, as the results of long-term ecological adaptability of summer flooding stress. The haplotypes of nuclear gene could be used for populations differentiation and germplasm protection. This identified gene flow and range dynamics have provided support for the gene-flow and geology hypothesis. It is also crucial for rescuing conservation to understand the impact of environmental dynamics on endangered organism evolution.